Experimental study on effect of N2 on physical parameters and phase equilibrium patterns of CO2-rich injection gas - QIN Nan, GAN Xiaofei, LUO Yu, LIU Xiaoxu, WEN Bin, CHEN Xingyu (Youqicang pingjia yu kaifa, 2025)
The high cost of industrial flue gas treatment makes injecting CO₂-rich exhaust gas into depleted oil and gas reservoirs a potential technology for enhanced recovery and carbon sequestration. This study aims to guide the injection process, and the effect of N2 on the physical properties of CO2-rich injection gas remains insufficiently understood. This study conducted experimental measurements of the physical parameters and phase equilibrium studies using a JEFRI phase analyzer and CPA (cubic plus association) equation of state. The results showed that at higher temperatures, the “opalescence phenomenon” in high CO2-rich injection gas was weaker and occurred at higher pressures. When temperature approached critical point, the opalescence was stronger but occurred at lower pressures, which were far from the critical pressure. When CO2-rich injection gas exhibited “opalescence phenomenon”, the fluid had critical point. However, the presence of a critical point did not necessarily imply observable opalescence, and no opalescence was observed when the fluid had no critical point. When the pressure was below 10 MPa, the fluid exhibited gas-like densities with volume decreasing rapidly as pressure increased. Above 20 MPa, the fluid showed liquid-like densities. The 10-20 MPa range represented a transition zone. At 2-55 MPa, the viscosities of five CO2-rich gas mixtures remained low, exhibiting gaseous characteristics. Under identical temperature and pressure conditions, as the N2 molar fraction increased from 10% to 90%, the deviation factor of CO2-rich injection gas increased while fluid density decreased. Thus, N2 content should be minimized during injection, and higher CO2 molar fractions improved injection performance. With 12 MPa as the threshold, viscosity increased with rising N2 content below 12 MPa but decreased with higher N₂ molar fraction above this pressure. A 5% O2 impurity had a negligible effect on the physical properties of CO2-rich injection gas and can be neglected. At the same composition, both deviation factor and viscosity of the injection gas first increased and then decreased with rising temperature, and the pressure intersection point varied with temperature and composition. By integrating experimental data with theoretical modeling, this study elucidates the effect of N2 on the physical properties of CO2-rich injection gas, providing guidance for enhanced recovery rate using flue gas or exhaust gas injection in oil and gas reservoirs.